Let us now praise famous men : three tenant families - Agee, James, 1909-1955.; Evans, Walker, 1903-1975. (Boston : Houghton Mifflin, 1988)
Words and photographs describe the daily lives of typical sharecropper families in the American South.
Originally published: Boston : Houghton Mifflin, 1941.
Library Journal.
Adult
Keywords: Agee, James, -- 1909-1955 -- Travel -- Alabama; Agee, James, -- 1909-1955 -- Travel; Farm tenancy -- Alabama -- History; Farm tenancy -- History; Alabama -- Description and travel; Alabama -- Rural conditions; Alabama -- Description and Travel; Alabama -- Rural conditions